Mapping trends in insecticide resistance phenotypes in African malaria vectors - Hancock, Penelope A.; Hendriks, Chantal J. M.; Tangena, Julie-Anne; Gibson, Harry; Hemingway, Janet; Coleman, Michael; Gething, Peter W.; Cameron, Ewan; Bhatt, Samir; Moyes, Catherine L. (PLOS Biology, 2020)
Malaria control efforts are threatened by the emergence of insecticide resistance in mosquito vector populations. This study provides fine-resolution maps of insecticide resistance levels in malaria vectors for large parts of Sub-Saharan Africa; the maps quantify recent spatial trends in resistance and can assist in the implementation of resistance management practices.